A Delphi Approach to Develop Sustainable Food System Metrics - Allen, Thomas; Prosperi, Paolo; Cogill, Bruce; Padilla, Martine; Peri, Iuri (Social indicators research, 2019)
Recurrent food crises and global environmental change are critical issues that pushed food security and sustainability to the top of the policy agenda. Policy-makers need assessment tools that help them decide what actions they should take to achieve these goals. This paper proposes a new metric system assessing the sustainability of food systems and diets at a subnational level adapted to the context of the Mediterranean area. Recognizing the systemic dimension of sustainability, the proposed information system builds on a vulnerability/resilience conceptual framework and considers the interactions between a set of biophysical and socioeconomic drivers of vulnerability and a number of context-specific food and nutrition security issues. A three-round iterative Delphi survey was conducted to involve a number of selected experts in the indicator selection process. 18 indicators were finally identified for eight preselected causal models of vulnerability and resilience at the interactions between a set of four drivers of change (water depletion, biodiversity loss, food price volatility, and changes in food consumption patterns) and four food and nutrition security outcomes (nutritional quality of food supply, affordability of food, dietary energy balance, and satisfaction of cultural food preferences). Each interaction was disentangled in exposure, sensitivity and resilience. The exercise allowed discussion of a conceptual and dynamic framework for food systems, and identification of indicators that gather consensus among the expert community.